2001
DOI: 10.1039/b102298a
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective amino acid recognition using acyclic thiourea receptors

Abstract: A series of acyclic thiourea derivatives, designed to create a cleft with four hydrogen bond donors suitable for carboxylate recognition, have been prepared, and their ability to bind to N-protected amino acid carboxylate salts has been investigated. The crystal structure of one of the thioureas has been determined showing that it forms a hydrogen bonded centrosymmetric dimer in the solid-state, in a conformation appropriate for the desired binding of carboxylates. The thioureas show good discrimination betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 12 publications
3
72
0
Order By: Relevance
“…In addition, the absence of any crosspeak between the alanine NHs and the pyridine aromatic protons in the rotating-frame Overhauser effect spectroscopy spectra indicates that the only conformation present in acetone has the two alanine NH protons in a reciprocal cis orientation (see Scheme 3c) and directed toward the interior of the macrocycle defined by the pseudopeptide. In this structure, which is similar to that found in the solid state (see below), it may be that the repulsive interaction between the lone pairs of the pyridine nitrogen atom and the amide carbonyl groups is minimized and the conformation is stabilized by attractive electrostatic interactions between the amide NHs and the pyridine nitrogen atom, as observed in similar systems (24)(25)(26)(27). The most relevant data for the calix [4]arene conformation in the two complexes are reported in Table 1, according to the standard rules (28).…”
Section: Synthesis and Conformational Properties Of The Receptors In supporting
confidence: 60%
See 3 more Smart Citations
“…In addition, the absence of any crosspeak between the alanine NHs and the pyridine aromatic protons in the rotating-frame Overhauser effect spectroscopy spectra indicates that the only conformation present in acetone has the two alanine NH protons in a reciprocal cis orientation (see Scheme 3c) and directed toward the interior of the macrocycle defined by the pseudopeptide. In this structure, which is similar to that found in the solid state (see below), it may be that the repulsive interaction between the lone pairs of the pyridine nitrogen atom and the amide carbonyl groups is minimized and the conformation is stabilized by attractive electrostatic interactions between the amide NHs and the pyridine nitrogen atom, as observed in similar systems (24)(25)(26)(27). The most relevant data for the calix [4]arene conformation in the two complexes are reported in Table 1, according to the standard rules (28).…”
Section: Synthesis and Conformational Properties Of The Receptors In supporting
confidence: 60%
“…The presence of crosspeaks in the rotating-frame Overhauser effect spectroscopy spectra (see Fig. 4, which is published as supporting information) between the signals of protons 2, 4, and 6 of the isophthaloyl aromatic nucleus and the alanyl amide protons supports the second hypothesis, where the equilibrating conformations differ for the reciprocal orientation (Scheme 3) of the NH protons, which can be trans (a) or cis-outside (b) and cis-inside (c) (22)(23)(24)(25)(26).…”
Section: Synthesis and Conformational Properties Of The Receptors In mentioning
confidence: 64%
See 2 more Smart Citations
“…Aryl(thio)ureas presenting two N-H groups are well recognized in the very active field of non-covalent organocatalysis for their ability to bind ketones, aldehydes and nitro groups through hydrogen bonding [2][3][4][5][6][7][8] . In addition, they are outstanding neutral compounds for the selective complexation of various anions [9][10][11][12][13][14] and they found application in the (enantio) selective extraction of carboxylate anions [15][16][17][18] . We have shown that some ureas and thioureas derived from 3-(2-aminophenyl)-4-methylthiazole-2(3H)-thione 1a enantioselectively bind to carboxylate anion derived from amino-acids 19 and act as organocatalysts for addition to aldehydes 20 .…”
Section: Introductionmentioning
confidence: 99%